Bacillus coagulans TL3 Inhibits LPS-Induced Caecum Damage in Rat by Regulating the TLR4/MyD88/NF-κB and Nrf2 Signal Pathways and Modulating Intestinal Microflora. (7th February 2022) - Wang, Yan; Lin, Jiaxi; Cheng, Ziyang; Wang, Tiancheng; Chen, Jia; Long, Miao
Abstract : Background . Bacillus coagulans has been widely used in food and feed additives, which can effectively inhibit the growth of harmful bacteria, improve intestinal microecological environment, promote intestinal development, and enhance intestinal function, but its probiotic mechanism is not completely clear. Aim . The aim of this study is to discuss the effect and mechanism of Bacillus coagulans TL3 on oxidative stress and inflammatory injury of cecum induced by LPS. Method . The Wistar rats were randomly divided into four groups, each containing 7 animals. Two groups were fed with basic diet (the LPS and control, or CON, groups). The remaining groups were fed with basic diet and either a intragastric administration high or low dose of B. coagulans, forming the HBC and LBC groups, respectively. The rats were fed normally for two weeks. On the 15th day, those in the LPS, HBC, and LBC groups were injected intraperitoneally with LPS—the rats in the CON group were injected intraperitoneally with physiological saline. After 4 hours, all the rats were anesthetized and sacrificed by cervical dislocation, allowing samples to be collected and labeled. The inflammatory and antioxidant cytokine changes of the cecum were measured, and the pathological changes of the cecum were observed, determining the cecal antioxidant, inflammation, and changes in tight junction proteins and analysis of intestinal flora. Result . The results show that LPS induces oxidative damage in the cecal tissues of rats and the occurrence of inflammation could also be detected in the serum. The Western blot results detected changes in the NF- κ B- and Nrf2-related signaling pathways and TJ-related protein levels. Compared with the LPS group, the HBC group showed significantly downregulated levels of expression of Nrf2, NQO1, HO-1, GPX, and GCLC. The expression of TLR4, MYD88, NF- κ B, IL-6, TNF α, and IL-1 β was also significantly downregulated, while the expression of other proteins (ZO-1, occludin, and claudin-1) increased significantly. Bacillus coagulans TL3 was also found to increase the relative abundance of the beneficial bacterium Akkermansia muciniphila in the intestines. There is also a significant reduction in the number of harmful bacteria Escherichia coli and Shigella (Enterobacteriaceae). Conclusion . Bacillus coagulans TL3 regulates the TLR4/MyD88/NF- κ B and Nrf2 signaling pathways in the cecal tissue of rats, protects the intestine from inflammation and oxidative damage caused by LPS, and inhibits the reproduction of harmful bacteria and promotes beneficial effects by regulating the intestinal flora bacteria grow, thereby enhancing intestinal immunity.